Hiperedi??o das trovas de Eul?lio Motta - Rocha, Juliana Pereira (2023)
This thesis, entitled Hyperedition of Eul?lio Motta?s trovas, financed by the Capes and inserted in the scope of the Graduate Program in Linguistic Studies - PPGEL, of the State University of Feira de Santana ? UEFS, problematizes philological praxis from of the editorial experience of the trovas by the Bahian writer Eul?lio de Miranda Motta, with due attention to the agents involved in the processes of production, propagation and circulation of the trovas in Brazil. The thesis? product is a website: O Trovador ? edition of the trovas by Eul?lio Motta (eulaliomottatrovador.com.br), wich is configured as a hyperedition of 337 trovas by Eul?lio Motta. He began his literary activity in the early 1920s and produced texts of different textual genres such as causos, poetry, chronicles, cord?is, trovas, etc. Among the literary genres practiced by the writer, the trovas stands out, which was present from the beginning of his literary activities until the year of his death in 1988. These texts were preserved in notebooks, dispersed manuscripts, typed and printed (books and newspapers), some of them unpublished. The methodology seeks to reconcile studies, philology methods with research within the scope of Digital Humanities, in the documentary sources of the collection and in the studies developed so far by researchers dedicated to the study of Eul?lio Motta. The research dialogues with the Sociology of Text, Textual Criticism, Digital Humanities and Literary Studies. With regard to oral tradition of the trovas, discussions on oral poetics and cultural studies are mobilized. To analyze the written tradition of the trovas, the research takes into account discussions on the Sociology of the Text and the cultural history of writing practices. Through the O Trovador website, the texts were presented under different approaches such as the facsimilar edition, the topographic edition, the linearized edition, the updated edition with links and the edition in synoptic confrontation (highlighted and not highlighted). Other contextual information about the trovas? production and circulation process, as well as the Trovista and Neotrovista movement in Brazil are also part of the website and can be accessed in a hypertextual manner, such as images, texts and videos. Thus, this research provides readersusers with an experience of immersion in the collection and literary production of Eul?lio Motta.